Wheat Cultivars With Contrasting Root System Size Responded Differently to Terminal Drought - Figueroa-Bustos, V.; Palta, J.A.; Chen, Y.; Stefanova, Katia; Siddique, K.H.M. (2020)
In the Mediterranean-type environment of Australia and other parts of the world, end-of- season or terminal drought is the most significant abiotic stress affecting wheat grain yields. This study examined the response of two wheat cultivars with contrasting root system size to terminal drought and the effect of terminal drought on grain yield and yield components. The cultivars were grown in 1.0 m deep PVC columns filled with soil in a glasshouse under well-watered conditions until the onset of ear emergence (Z51) when well-watered and terminal drought treatments were imposed. Terminal drought reduced stomatal conductance, leaf photosynthesis, and transpiration rates faster in Bahatans-87 (larger root system size) than Tincurrin (smaller root system size). Terminal drought reduced grain yield in both cultivars, more so in Bahatans-87 (80%) with the large root system than Tincurrin (67%) with the small root system, which was mainly due to a reduction in grain number and grain size in Bahatans-87 and grain size in Tincurrin. In the terminal drought treatment, Bahatans-87 had 59% lower water use efficiency than Tincurrin, as Bahatans-87 used 39% more water and reduced grain yield more than Tincurrin. The lesser reduction in grain yield in Tincurrin was associated with slower water extraction by the small root system and slower decline in stomatal conductance, leaf photosynthesis, and transpiration rates, but more importantly to faster phenological development, which enabled grain filling to be completed before the severe effects of water stress.